Railway maintenance windows: Discrepancies between planning and practice in Sweden - Daria Ivina; Carl-William Palmqvist (Transportation Research Interdisciplinary Perspectives, 2023)
Efficient and timely maintenance is essential for the robust operation of infrastructure across all types of transport. In the railway sector, track maintenance presents unique challenges. Specifically, some maintenance tasks require track closures, which can disrupt train schedules. Coordinating these closures with regular train operations makes the scheduling process complicated. To ensure sufficient time for maintenance and prevent conflicts with train operations, the Swedish Transport Administration introduced “maintenance windows.” Maintenance windows, ranging from two to six hours, are periods designated for maintenance, with the track free from train operations. They are set before finalizing the annual train timetable. In this study, we examined the practical application of maintenance windows on a railway line in Southern Sweden from 2019 to 2020. Our findings reveal that while 10% of the total line capacity was allocated for maintenance windows, 11% of the capacity was used for maintenance. Alarmingly, 68% of trackwork occurred outside maintenance windows, and only 34% of the reserved maintenance window capacity was utilized. There is a significant discrepancy between the time and location reserved for maintenance windows and their actual utilization. To address this, we propose aligning maintenance windows more closely with contractor needs by 1) incorporating maintenance windows on the weekends, 2) making maintenance windows available closer to the end of the planning horizon, 3) extending the duration of some maintenance windows, and 4) designing and integrating incentives to encourage contractors to operate within planned maintenance windows.